Mechanical behavior of ultrathin sputter deposited porous amorphous Al2O3 films. (15th February 2017) - van der Rest, Astrid; Idrissi, Hosni; Henry, Frédéric; Favache, Audrey; Schryvers, Dominique; Proost, Joris; Raskin, Jean-Pierre; Van Overmeere, Quentin; Pardoen, Thomas
Abstract: The determination of the mechanical properties of porous amorphous Al2 O3 thin films is essential to address reliability issues in wear-resistant, optical and electronic coating applications. Testing the mechanical properties of Al2 O3 films thinner than 200 nm is challenging, and the link between the mechanical behavior and the microstructure of such films is largely unknown. Herein, we report on the elastic and viscoplastic mechanical properties of amorphous Al2 O3 thin films synthesized by reactive magnetron sputtering using a combination of internal stress, nanoindentation, and on-chip uniaxial tensile testing, together with mechanical homogenization models to separate the effect of porosity from intrinsic variations of the response of the sound material. The porosity is made of voids with 2–30 nm diameter. The Young's modulus and hardness of the films decrease by a factor of two when the deposition pressure increases from 1.2 to 8 mTorr. The contribution of porosity was found to be small, and a change in the atomic structure of the amorphous Al2 O3 matrix is hypothesized to be the main contributing factor. The activation volume associated to the viscoplastic deformation mechanism is around 100 Å 3 . Differences in the atomic structure of the films could not be revealed by electron diffraction, pointing to a minute effect of atomic arrangement on the elastic properties. Graphical abstract: Image 1